Enhanced Immune Responses Conferring Cross-Protection by Skin Vaccination With a Tri-Component Influenza Vaccine Using a Microneedle Patch - Zhu, Wandi; Li, Song; Wang, Chao; Yu, Guoying; Prausnitz, Mark R.; Wang, Bao-Zhong (Frontiers in Immunology, 2018)
Skin vaccination using biodegradable microneedle patch (MNP) technology in vaccine delivery is a promising strategy showing significant advantages over conventional flu shots. In this study, we developed an MNP encapsulating a 4M2e-tFliC fusion protein and two types of whole inactivated influenza vaccines, H1N1 and H3N2, as a universal vaccine candidate. We demonstrated that mice receiving this tri-component influenza vaccine via MNP acquired improved IgG1 antibody responses with more balanced IgG1/IgG2a antibody and enhanced cellular immune responses, including increased populations of IL-4 and IFN-γ producing cells and higher frequencies of antigen-specific plasma cells compared to intramuscular (IM) injection. In addition, stronger germinal center reactions, increased numbers of langerin-positive migratory DCs and increased cytokine secretion were observed in the skin draining lymph nodes after immunization with the tri-component influenza MNP vaccine. The MNP immunized group also possessed enhanced protection against a heterologous reassortant A/Shanghai/2013 H7N9 (rSH) influenza virus infection. Furthermore, the sera collected from 4M2e-tFliC MNP-immunized mice were demonstrated to have antiviral efficacy against reassortant A/Vietnam/1203/2004 H5N1 (rVet) and A/Shanghai/2013 H7N9 (rSH) virus challenges. The immunological advantages of skin vaccination with this tri-component MNP vaccine could offer a promising approach to develop an easily applicable and broadly protective universal influenza vaccine.